The Development of Market-Driven Identities in Young People: A Socio-Ecological Evolutionary Approach - Butler, Stephen (Frontiers in Psychology, 2021)
With the transition toward densely populated and urbanized market-based cultures over the past 200 years, young people’s development has been conditioned by the ascendancy of highly competitive skills-based labour markets that demand new forms of embodied capital (e.g, education) for young people to succeed. Life-history analysis reveals parental shifts toward greater investment in fewer children so parents can invest more in their children’s embodied capital for them to compete successfully. Concomitantly, the evolution of market-based capitalism has been associated with the rise of extrinsic values such as individualism, materialism and status-seeking, which have intensified over the last forty to fifty years in consumer economies. The dominance of extrinsic values is consequential: when young people show disproportionate extrinsic relative to intrinsic values there is increased risk for mental health problems and poorer well-being. This paper hypothesizes that, concomitant with the macro-cultural promotion of extrinsic values, young people in advanced capitalism (AC) are obliged to develop an identity that is market-driven and embedded in self-narratives of success, status, and enhanced self-image. The prominence of extrinsic values in AC are synergistic with neuro-maturational and stage-salient developments of adolescence and embodied in prominent market-driven criterion such as physical attractiveness, displays of wealth and material success, and high (educational and extra-curricular) achievements. Cultural transmission of market-driven criterion is facilitated by evolutionary tendencies in young people to learn from older, successful and prestigious individuals (prestige bias) and to copy their peers. The paper concludes with an integrated socio-ecological evolutionary account of market-driven identities in young people, while highlighting methodological challenges that arise when attempting to bridge macro-cultural and individual development.